Aesthetic experience of beautiful and ugly persons: a critique. Issue 1 (1st January 2016) - Suojanen, Mika
Abstract : The question of whether or not beauty exists in nature is a philosophical problem. In particular, there is the question of whether artworks, persons, or nature has aesthetic qualities. Most people say that they care about their own beauty. Moreover, they judge another person's appearance from an aesthetic point of view using aesthetic concepts. However, aesthetic judgements are not objective in the sense that the experience justifies their objectivity. By analysing Monroe C. Beardsley's theory of the objectivity of aesthetic qualities, I examine whether there are really beautiful and ugly persons in the world. I will criticize the way analytic philosophers judge people and art from an aesthetic perspective. If there are no aesthetic qualities in the world, nobody can judge someone beautiful or ugly without oppression. Aesthetic judgement is exercise of power.